2020
DOI: 10.3897/bdj.8.e49285
|View full text |Cite
|
Sign up to set email alerts
|

Bee species checklist of the San Francisco Peaks, Arizona

Abstract: Here we present a checklist of the bee species found on the C. Hart Merriam elevation gradient along the San Francisco Peaks in northern Arizona. Elevational gradients can serve as natural proxies for climate change, replacing time with space as they span multiple vegetation zones over a short geographic distance. Describing the distribution of bee species along this elevation gradient will help predict how bee communities might respond to changing climate. To address this, we initiated an inventory associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…In a previous study we identified seven species of habitat generalists out of 86 species of Megachilidae, characterized as being found in at least three different vegetation/elevation zones ((McCabe et al 2020): Appendix S1: Table S3). Rather, species that have a narrow range of habitat along this gradient are more likely to be more vulnerable to climate change (Markle and Kozak 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study we identified seven species of habitat generalists out of 86 species of Megachilidae, characterized as being found in at least three different vegetation/elevation zones ((McCabe et al 2020): Appendix S1: Table S3). Rather, species that have a narrow range of habitat along this gradient are more likely to be more vulnerable to climate change (Markle and Kozak 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Many bee species in the family Megachilidae nest above ground in cavities that are likely to be close to ambient temperatures (Wilson 2019), while ground nesters may be more buffered from ambient temperature changes due to their nesting substrate (Danforth et al 2019). With its dramatic elevational gradient and well studied bee fauna, the San Francisco Peaks of Coconino County, Arizona, are an ideal study system to examine climate change and how it will impact high-elevation bee communities (McCabe et al 2020). We hypothesized that: (1) Bee species in the family Megachilidae moved to lower elevations (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Located in northern central Arizona, ~20 miles north of Flagstaff (35.341031 N, −111.683217 W), the San Francisco Peaks is an especially important elevation gradient with high insect pollinator diversity, including at least ~360 native bee species [48]. The San Francisco Peaks make up one of two dozen "sky islands" in the southwest United States, or isolated mountain tops, that serve as biodiversity hotspots due to the multiple habitats present along the altitudinal gradient [49,50].…”
Section: Study Location and Sampling Methodsmentioning
confidence: 99%
“…All insects were initially identified in the Northern Arizona University (NAU) pollinator lab and digitally catalogued in the Symbiota Collection of Arthropods Network (SCAN) online database. Bees were identified using published identification guides (see methods from McCabe et al [48]). Classification for species Melissodes and Andrena followed LaBerge [52][53][54] with modifications from Wright's work on Melissodes [55,56].…”
Section: Species Identificationmentioning
confidence: 99%
See 1 more Smart Citation